Thromboangiitis obliterans (Buerger disease) - Seebald, Jessica (Radiol Case Rep, 2015)
Thromboangiitis obliterans (Buerger disease) is an occlusive, nonatherosclerotic, inflammatory vasculitis that causes ischemia in small and medium vessels. Most commonly, Buerger disease is diagnosed in 40- to 45-year-old men with a heavy smoking history. Our case exemplifies the most common presentation, diagnosis, and treatment in a 53-year-old male smoker who presents with arm pain and dusky cool fingers. A Buerger diagnosis requires exclusion of autoimmune, diabetic, and embolic causes. The only recognized treatment for this disease is smoking cessation.